Identification of cellular intermediates unveils unique enzymes for flagellar glycan biosynthesis in Clostridioides difficile - Paul J. Hensbergen; Bob van Puffelen; Nina Musch; Augustinus N. A. Ammerlaan; Paul L. C. Zuidgeest; Loes van Huijkelom; Rembrandt J. V. Kanbier; Maaike M. Vet; Xuan S. Zheng; Pranav V. N. Bhamidipati; Martin F. Larralde; Niek Blomberg; et al. (Proceedings of the National Academy of Sciences, 2026)
Glycosylation of bacterial surface proteins, such as flagellin (FliC), is important for their function and is often involved in virulence of pathogens. Glycans can be further modified by so-called postglycosylation modifications (PGMs), often resulting in exclusive molecular structures. In Clostridioides difficile, a unique glycan structure (Type A) decorates FliC (which forms the flagellar filament) that consists of an O -linked N -acetyl-β- d -glucosamine (GlcNAc) modified with an N -methyl-L-threonine via a phosphodiester linkage. This PGM is synthesized by a set of four enzymes encoded in one operon ( ftaABCD ), but the exact biosynthesis pathway and biosynthetic intermediates remain unknown. In this study, we chemically synthesized two hitherto undescribed biosynthetic intermediates that we predicted based on bioinformatic analyses, CDP-threonine and CDP- N -methylthreonine. We showed that they are involved in the Type A PGM biosynthesis, as evidenced by mass spectrometric analyses of extracts of a set of C. difficile mutant strains. Furthermore, we characterized FtaC to be a SAM-dependent CDP-threonine N -methyltransferase that installs the methyl group on CDP-threonine prior to transfer of the PGM to GlcNAc-FliC, and we revealed FtaD as the CDP- N -methylthreonine:GlcNAc N -methylthreoninephosphotransferase. Finally, using recombinantly expressed FtaC and FtaD in combination with synthetic CDP-threonine, we reconstituted the biosynthesis pathway of the Type A PGM in vitro. Overall, our results open avenues to explore these unique biosynthesis enzymes in molecular detail to provide new points of entry for the development of biosynthesis inhibitors and tools to study the role of this PGM in virulence and flagellar function.